Community Structure and Abundance of Archaea in a Zostera marina Meadow: A Comparison between Seagrass-Colonized and Bare Sediment Sites. (18th November 2019) - Zheng, Pengfei; Wang, Chuantao; Zhang, Xiaoli; Gong, Jun
Abstract : Seagrass colonization alters sediment physicochemical properties by depositing seagrass fibers and releasing organic carbon and oxygen from the roots. How this seagrass colonization-induced spatial heterogeneity affects archaeal community structure and abundance remains unclear. In this study, we investigated archaeal abundance, diversity, and composition in both vegetated and adjacent bare surface sediments of a Zostera marina meadow. High-throughput sequencing of 16S rDNA showed that Woesearchaeota, Bathyarchaeota, and Thaumarchaeota were the most abundant phyla across all samples, accounting for approximately 42%, 21%, and 17% of the total archaeal communities, respectively. In terms of relative abundance, Woesearchaeota and Bathyarchaeota were not significantly different between these two niches; however, specific subclades (Woese-3, Woese-21, Bathy-6, Bathy-18) were significantly enriched in vegetated sediments (P < 0.05 ), while Thaumarchaeota was favored in unvegetated sites (P = 0.02 ). The quantification of archaeal 16S rRNA genes showed that the absolute abundance of the whole archaeal community, Bathyarchaeota, and Woese-3, Woese-10, Woese-13, and Woese-21 was significantly more abundant in vegetated sediments than in bare sediments (P < 0.05 ). Our study expands the available knowledge of the distribution patterns and niche preferences of archaea in seagrass systems, especially for the different subclades of Woesearchaeota and Bathyarchaeota, in terms of both relative proportions and absolute quantities.